Territorialisation, Deterritorialisation and Power in Democratic Assemblages - Kaithwar, Raj (Theoria (Pietermaritzburg), 2025)
Democracy as an assemblage highlights the complexity, contingency and non-linear becomings of a democratic society which is never static but constantly transforming. This article contends that there is a need for an explicit engagement with power in democratic assemblages. It is argued that power is not an individual possession but a function of assemblages, operating through territorialisation and deterritorialisation. These processes, through the flow of power as discipline, production, and disruption, shape democracy. Analysing liberal democracy as a territorialised democratic assemblage, the article states that it faces deterritorialisation by nature's dynamism and ecological thought. However, rather than collapsing in the face of these lines of flight, democracy carries the potential to reterritorialise as ecological democracy by adapting new configurations of power, nature and governance.